Improvement of the chemical resistance of zirconium fluoride glasses coated with a Tiron (R) modified tin oxide layer prepared by the sol-gel process - Hammer, Peter [UNESP]; Rizzato, A. P.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Elsevier B.V., 2006)
In order to improve the chemical resistance of zirconium fluoride glass a protective transparent SnO2 layer was deposited by the solgel dip-coating process in the presence of Tiron (R) as particle surface modifier agent. After water immersion for different periods of time, both coated and non-coated fluoride glasses were analyzed by scanning electron microscopy, mass loss evaluation, infrared spectroscopy and X-ray photoelectron spectroscopy. In contrast to the effects occurring for non-coated glass, where the surface undergoes a rapid selective dissolution of the most soluble species, the results for the SnO2-coated glass showed that the filling of the film nanopores by dissolved glass material results in a hermetic barrier protecting the glass surface. The selective glass dissolution was confirmed by liquid chromatography measurements of the etching solution after each exposure time. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chemical durability; corrosion; flims and coatings; infrared glasses; fluorides; scanning electron microscopy; nanoparticles; FTIR measurements; tin oxide; XPS